Two new species of the feather mite subfamily Pterodectinae (Acari: Astigmata: Proctophyllodidae) from Brazil - Hernandes, Fábio A. [UNESP]; Valim, Michel P. (My University, 2006)
We describe two new pterodectine feather mites (Analgoidea: Proctophyllodidae) from Brazilian passerines (Passeriformes): Pterodectes amaurochalinus sp. n., from Turdus amaurochalinus Cabanis (Turdidae), and Dolichodectes neotropicus sp. n., collected from Elaenia chiriquensis Lawrence (Tyrannidae). A key to species of the genus Dolichodectes is presented. Copyright © 2006 Magnolia Press.
Keywords: Analgoidea; Astigmata; Brazil; Dolichodectes; Feather mite; Pterodectes; Systematics; Acari; Elaenia chiriquensis; Passeri; Passeriformes; Proctophyllodidae; Turdidae; Turdus amaurochalinus; Tyrannidae